BIODIVERSITATEA VEGETALĂ A TERENURILOR DEGRADATE DIN COMUNA TOHATIN - USM ADMIN (Studia Universitatis Moldaviae: Stiinte reale si ale naturii, 2011)
The analysis of vegetation from Tohatin village shows 55 species of Magnoliophytes, belonging to 49 genus and 16 biological families. Most frequently there are Asteraceae family with 24 species from 20 genus, which dominates not only by diversity, but also by the abundance of typical species: Cyclachaena xanthiifolia and Xanthium californicum. Poaceae family are presented with 5 species from 4 genus, frequently there are species of Elytrigia repens, Bromus arvensis and Lolium perenne.